High-performance HRM practices and organizational commitment: An empirical study of banking employees in Bangladesh - Aktar, Alima; Pangil, Faizuniah (2017)
Organizational Commitment (OC) refers to the employees’ strong desire, need or feelings of obligation to stay and identify them within the organization.The primary objective of this study is to investigate the relationship between high-performance HRM practices and OC in the context of banking employee in Bangladesh.Cross-sectional survey data has been collected from 376 employees who working in different private commercial banks in Bangladesh.This study employed Smart PLS 3.0 version software to analyze the hypothesized path modeling.The results of structural equation modeling revealed that high-performance work practices namely training & development, employee participation, and rewards and recognition were significantly associated with OC.Findings of this study help practitioners to understand the factors that have the positive association with OC which indicates that organizations should ensure a healthy working environment to make their employees highly attached to the organization and reduce the voluntary intention of leaving the organizations.